1997
DOI: 10.1111/j.1439-0442.1997.tb01143.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Progestagen Assays for Measuring Progesterone Metabolites in Faeces of the Bitch

Abstract: Summary From 12 bitches of various breeds with fertile oestrus cycles faecal samples were collected daily from the onset of pro‐oestrus till 20 days after the start of vulval bleeding, then once per week till about 1 week before term. Immunoreactive progesterone metabolites were extracted from the samples using methanol and measured using immunoassays. In a first experiment four different assays were compared in regard to the amounts of immunoreactive substances measured: the enzyme immunoassay against 20‐oxo‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…HPLC analysis suggested that fecal progestins in the black-footed ferret consist of a single conjugated and several unconjugated progestins, with native progesterone accounting for <10% of the total immunoreactivity [Brown, 1997]. The unconjugated progestins probably are reduced pregnanes, as has been described for other carnivores [Möstl et al, 1993;Brown et al, 1994;Monfort et al, 1997;Möstl and Brunner, 1997]. The antibody used in this EIA has been shown by HPLC to cross-react with several progestins that have similar retention times to pregnanes and hydroxyprogesterones in feces of the red wolf (Canis rufus) [Walker, 1999].…”
Section: Discussionmentioning
confidence: 81%
“…HPLC analysis suggested that fecal progestins in the black-footed ferret consist of a single conjugated and several unconjugated progestins, with native progesterone accounting for <10% of the total immunoreactivity [Brown, 1997]. The unconjugated progestins probably are reduced pregnanes, as has been described for other carnivores [Möstl et al, 1993;Brown et al, 1994;Monfort et al, 1997;Möstl and Brunner, 1997]. The antibody used in this EIA has been shown by HPLC to cross-react with several progestins that have similar retention times to pregnanes and hydroxyprogesterones in feces of the red wolf (Canis rufus) [Walker, 1999].…”
Section: Discussionmentioning
confidence: 81%
“…Samples were extracted and analysed according to Möstl and Palme's (2008) protocol using an enzyme immunoassay for 9.3 11-oxoaetiocholanolone (Lab-code: 72-alt, Palme and Möstl 1997 ) previously validated for use in cats ( Palme and others 2001 ). In the current study, interassay and intra-assay coefficients of variation were 8.9 per cent (n=12) and 3.5 per cent (n=383), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In other carnivore species, i.e. the domestic dog, luteal phases were monitored analyzing fecal progesterone metabolites [27,28], whereas the pregnanediol assay used in our study on sun bears was found to be less suitable [28]. Additionally, in the dog, androgen metabolites are excreted into the feces during the follicular phase [27,29].…”
Section: Discussionmentioning
confidence: 98%